Pengaruh Inflasi Terhadap Pembagian Dividen Pada BUMN : Studi Kasus Sektor Pertambangan - Dodi Firman Syah; Haryadi .; Siti Hodijah; Nurhayani . (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the influence of State Capital Participation (PMN) and inflation on dividend policy in mining companies during the 2020–2024 period. The analytical method used is a panel regression with a fixed effects approach on four state-owned enterprises (SOEs), resulting in a total of 20 observations. The estimation results show that the model is able to significantly explain variations in dividend changes, with an R-squared value of 0.9279, while the F-statistic is 36.037 with a significance level of 0.0000, indicating that the independent variables simultaneously influence dividends. Partially, PMN has a negative and significant effect on dividends, with a coefficient of –0.4381 and a probability value of 0.0000, indicating that an increase in PMN has the potential to reduce dividend payments. Meanwhile, the inflation variable shows a positive but insignificant effect on dividends, with a coefficient of 1.0471 and a probability value of 0.0908. These findings indicate that internal company factors related to PMN funding policies play a dominant role in determining dividend amounts, compared to external macroeconomic factors such as inflation. The resulting regression model is: DIVIDEND = 7.8311 – 0.4381PMN + 1.0472Inflation. The results of this study also imply that increasing PMN allocations must be balanced with operational and profitability strategies to avoid suppressing the company's ability to distribute dividends